Dredging proceedings of the symposium organized by the Institution of Civil Engineers in London 18th October 1967. (Institution of Civil Engineers, 1968)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium held on 18 October 1967.